Experimental study on consistency of the impact performance between composite beams and reinforced concrete beams. (15th March 2023) - Liao, Weizhang; Liu, Kaixin; Ma, Chao; Liang, Jichao
Graphical abstract: Highlights: Different impact energies were selected based on the absorption energy of beams under static loading. The difference in impact performance between reinforced concrete and reinforced concrete composite beams was tested. The damage assessment method based on the residual deformation under impact loadings was proposed. The impact performance of the reinforced concrete beams and reinforced concrete composite beams can be treated as the same within the tested impact loadings. Abstract: Composite (CC) beams are employed more and more extensively because of their advantages in environmentally-friendly and rapid construction. These beams are possibly subjected to impact loadings due to occasional accidents or terrorist attacks during the service. It should be clarified whether the previous research achievements on the impact performance of reinforced concrete (RC) beams can be directly applied to CC beams. Five groups of full-scale CC beams and RC beams were fabricated with the same reinforcement ratios. One group of these specimens was tested under static bending loading, and the other eight specimens were tested under impact loading through the drop hammer test system. The failure modes, deformation, and force response of CC beams and RC beams were compared. The experimental results presented that the failure modes of CC beams are consistent with those of RC beams in the impact energy range of 1.0 E s ∼ 3.5 E s . The increasing impact energy changes the failure mode of CC beams from flexure failure to flexure‐shear failure until shear failure. With the increase of impact energy from 1.0 E s to 3.5 E s, the residual deformation increases first and then decreases, and the impact force of CC beams and RC beams are increased by 55.9% and 78.2%. There is little difference between CC beams and RC beams in peak deformation and residual deformation, a similar trend is found in impact force and support reaction force. Moreover, the beams can perform well impact resistance in the range of 1.0 E s ∼ 2.3 E s . Based on the residual deformation under impact loading and the deformation under static loading, the damage assessment method was proposed to evaluate the damage level of beams subjected to impact loadings.